Monitoring and integrated care coordination of patients with alpha-mannosidosis: A global Delphi consensus study - Guffon, Nathalie; Burton, Barbara K; Ficicioglu, Can; Magner, Martin; Gil-Campos, Mercedes; Lopez-Rodriguez, Monica A; Jayakar, Parul; Lund, Allan M; Tal, Galit; Garcia-Ortiz, Jose Elias; Stepien, Karolina M; Ellaway, Carolyn; et al. (Molecular genetics and metabolism, 2024)
INTRODUCTION: Current literature lacks consensus on initial assessments and routine follow-up care of patients with alpha-mannosidosis (AM). A Delphi panel was conducted to generate and validate recommendations on best practices for initial assessment, routine follow-up care, and integrated care coordination of patients with AM. METHODS: A modified Delphi method involving 3 rounds of online surveys was used. An independent administrator and 2 nonvoting physician co-chairs managed survey development, anonymous data collection, and analysis. A multidisciplinary panel comprising 20 physicians from 12 countries responded to 57 open-ended questions in the first survey. Round 2 consisted of 11 ranking questions and 44 voting statements. In round 3, panelists voted to validate 60 consensus statements. The panel response rate was ≥95% in all 3 rounds. Panelists used 5-point Likert scales to indicate importance (score of ≥3) or agreement (score of ≥4). Consensus was defined a priori as ≥75% agreement with ≥75% of panelists voting. RESULTS: Consensus was reached on 60 statements, encompassing 3 key areas: initial assessments, routine follow-up care, and treatment-related follow-up. The panel agreed on the type and frequency of assessments related to genetic testing, baseline evaluations, quality of life, biochemical measures, affected body systems, treatment received, and integrated care coordination in patients with AM. Forty-nine statements reached 90% to 100% consensus, 8 statements reached 80% to 85% consensus, and 1 statement reached 75% consensus. Two statements each reached consensus on 15 baseline assessments to be conducted at the initial follow-up visit after diagnosis in pediatric and adult patients. CONCLUSION: This is the first Delphi study providing internationally applicable, best-practice recommendations for monitoring patients with AM that may improve their care and well-being.
Keywords: delfská metoda; Delivery of Health Care, Integrated; průzkumy a dotazníky; Surveys and Questionnaires; alfa-mannosidóza; Best practice; Monitoring; konsensus; alpha-Mannosidosis; Alpha-mannosidosis; Follow-up; Consensus; Humans; Delphi; International; lidé; integrované poskytování zdravotní péče; Delphi Technique